Onder kunstenaars en organisaties = Among artists and organisations - Beerten, Katelijne; Boelen, Jan; Huybrechts, Liesbeth (Hasselt : Platform Beeldende Kunsten Limburg Hasselt, 2005)
Arink, Karin ; Atelier van Lieshout ; Bailly, Virginie ; Van Bergen, Jeroen ; Boldyreff, Olga ; Clarysse, Johan ; Cobbing, William ; Coolen, Caroline ; Van Dingenen, Filip ; van Eetvelde, Catharina ; Emin, Tracey ; Gillen, Tina ; Gonnissen, Willo ; de Gruyter, Voebe ; Hoeben, Marcel ; Hulsmans, Peter ; Hurkmans, Rini ; Van Ingelgom, Ignace ; Jap Lim, Peter ; Kaizman, Boaz ; Killaars, Fransje ; Körmeling, John ; Mackert, Suska ; Maes, Ives ; Minnen, Raymond ; Oosting, Alien ; Orta, Lucy ; Robijns, Gert ; Rombouts, Guy ; Roosen, Maria ; Schuil, Han ; Street, Kate ; Visic, Loreta ; Visser, Carel ; Vrancken, Kristof ; Wastijn, Koen
boek